ANALISIS KEBUTUHAN MASYARAKAT TERHADAP RUMAH SAKIT BERBASIS SYARIAH BERDASAKAN SIKAP - Sitti Nur Djannah; Rochana Ruliyandari (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2020)
The needs of the community for health services are increasingly high, this is due to increased public awareness of the meaning of health. Health and health services are one of the important needs for humans. Hospitals must be able to provide health services to the community. One of them is the existence of sharia-based hospitals and in accordance with the certifications and standards set by MUKISI. However, the problem in the community is that the Islamic hospital is inflexible with regard to non-Muslim and Muslim patient services and principles Islamic hospital. So this study aims to determine community needs for Islamic hospitals based on attitude. To see whether people need an Islamic hospital as an important health facility or not. Using observational analytic method with quantitative descriptive approach. This research was conducted in the Umbulharjo area of Yogyakarta City, using random sampling techniques, using a questionnaire. Themajority of people agree with the existence of sharia hospitals and the principles applied by sharia-based hospitals. And people need sharia hospitals that are flexible and continue to provide the best health services in accordance with Islamic sharia without reducing the quality of services and care provided. It can be concluded that the community chooses to agree and is in dire need of sharia hospitals, which can provide services and education both medical and spiritual and provide the best services for Muslim and non-Muslim patients. Keywords: attitude, health, needs, hospitals, sharia hospitals